2015
DOI: 10.1002/gete.201400010
|View full text |Cite
|
Sign up to set email alerts
|

Soil‐structure interaction in tunnel lining analyses

Abstract: There are various methods for the analysis of the interactional behavior of the surrounding land, using the lining structure which is the most common method of deigning lining structure tools for the static loads by using the hyper static methods. In recent years, there has been a question that depicts whether this method provides the best results in designing the tunnel structure or not. Due to the nonlinear behavior of the earth surrounding the lining structure, utilizing the lining method could lead to cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 7 publications
0
12
0
2
Order By: Relevance
“…Similarly, the stress components of any point in the surrounding rock mass can be solved by substituting (14) into (7).…”
Section: Complex Variable Methods For Linedmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, the stress components of any point in the surrounding rock mass can be solved by substituting (14) into (7).…”
Section: Complex Variable Methods For Linedmentioning
confidence: 99%
“…The stresses of the lining and surrounding rock mass can be determined using (7) once the six analytic functions are determined. And then the displacement can be determined using (11) and (12).…”
Section: Complex Variable Methods For Linedmentioning
confidence: 99%
See 2 more Smart Citations
“…This coincides with the research of Rott et al where they found that the ratio of horizontal and vertical displacements are highly influenced by the values of K 0 . Möller and Vermeer and Behnen et al highlighted the importance of modeling soil‐structure interaction in tunneling simulation, which affects the stress distribution around the tunnel and induces effects to the ground surface. However, the components that contribute to surface volume loss during tunneling process are not clearly elaborated, and there is no study on the evaluation of the influence of tunnel volume loss on the surface volume loss by taking into account the contribution of soil compressibility, as well as elasticity, and plasticity of soil.…”
Section: Introductionmentioning
confidence: 99%